Suprasternal access for transcatheter aortic valve implantation: All ways lead to Rome. Issue 6 (18th May 2020) - Saia, Francesco; Leone, Alessandro
Key Points: What the article teaches . Suprasternal (SS) access to the innominate artery is an easy and very safe approach for transcatheter aortic valve implantation (TAVI) when transfemoral (TF) access is not feasible. How it will impact practice . In experienced hands, SS TAVI could become the preferred alternative approach for non‐TF TAVI. What new research/study would help answer the question posed . The hypothesis of superior safety of SS access for TAVI in comparison with other non‐TF approaches should be investigated in dedicated studies.